Towards addressing the current state of confusion within the Hexabothriidae Price, 1942 (1908): Callorhynchocotyle Suriano & Incorvaia, 1982 (Monogenea: Hexabothriidae) re-visited, with the preliminary evaluation of novel parameters for measuring haptoral armature of hexabothriids - Vaughan, David; Christison, Kevin (Zootaxa, 2012)
The monogenean family, Hexabothriidae Price, 1942 (1908), currently consists of 15 valid genera parasitic on the gills ofchondrichthyan fishes. The hexabothriid literature is littered with inconsistencies, ambiguity and editorial errors whichhampers the progress and the development of investigations after the significant treatment of the family by Boeger &Kritsky (1989). A lack of consistency in the measurement protocol for the haptoral armature of hexabothriids is highlight-ed and discussed. The preliminary results of a new measurement protocol incorporating existing and novel parameterswere explored for the first time using statistical analyses. Character variables were investigated for their utility as poten-tially useful discriminators using univariate and multivariate analyses. The elimination of age-associated variance in suck-er sclerites was performed by ratio-transformation of the data to an age-dependant variable. Character variables with ahigh coefficient of variance after accounting for age were disqualified for use in the subsequent analyses. A coefficient ofvariance exceeding a conservative 10% limit was considered the result of measurement error resulting from the small sizesof these variables and therefore may also reflect the limitations of hardware and software in making small but accuratemeasurements. The proposed protocol is tested on representatives of Callorhynchocotyle and a Rajonchocotyle species totest the utility of character variables in separating species. Principle Component Analysis of the combination of the sucker-sclerites and the hamulus provided a preliminary level of robustness in separating Callorhynchocotyle species with theexception of Callorhynchocotyle hydrolagi for which there were insufficient data. Results confirm the importance of thehamulus in providing valuable diagnostic significance but the shape of the sucker sclerites as a function of total length anddiameter may also provide significant potential. Callorhynchocotyle is revisited with the addition of new specimens for 3of the species. The new data resulting from the measurement protocol are included in the redescription of Callorhynchoc-otyle marplatensis, Callorhynchocotyle callorhynchi and Callorhynchocotyle amatoi. Supplemental information is provided for C. hydrolagi and Callorhynchocotyle sagamiensis.